Bilateral impairments of shoulder abduction in chronic hemiparesis: Electromyographic patterns and isokinetic muscle performance - Avila M.A. (2013)
Objective: To analyze electromyographic (EMG) patterns and isokinetic muscle performance of shoulder abduction movement in individuals who sustained a cerebrovascular accident (CVA). Design: Twenty-two individuals who sustained a CVA and 22 healthy subjects volunteered for EMG activity and isokinetic shoulder abduction assessments. EMG onset time, root mean square (RMS) for upper trapezius and deltoid muscles, as well as the isokinetic variables of peak torque, total work, average power and acceleration time were compared between limbs and groups. Results: The paretic side showed a different onset activation pattern in shoulder abduction, along with a lower RMS for both muscles (21.8 ± 13.4% of the maximal voluntary isometric contraction (MVIC) for the deltoid and 25.9 ± 15.3% MVIC for the upper trapezius, about 50% lower than the control group). The non-paretic side showed a delay in both muscles activation and a lower RMS for the deltoid (32.2 ± 13.7% MVIC, about 25% lower than the control group). Both sides of the group of individuals who sustained a CVA presented a significantly lower isokinetic performance compared to the control group (paretic side ∼60% lower; non-paretic side ∼35% lower). Conclusions: Shoulder abduction muscle performance is impaired in both paretic and non-paretic limbs of individuals who sustained a CVA. © 2012 Elsevier Ltd.